2007
DOI: 10.1073/pnas.0700477104
|View full text |Cite
|
Sign up to set email alerts
|

Soluble misfolded subfractions of mutant superoxide dismutase-1s are enriched in spinal cords throughout life in murine ALS models

Abstract: Mutants of superoxide dismutase-1 (SOD1) cause ALS by an unidentified cytotoxic mechanism. We have previously shown that the stable SOD1 mutants D90A and G93A are abundant and show the highest levels in liver and kidney in transgenic murine ALS models, whereas the unstable G85R and G127X mutants are scarce but enriched in the CNS. These data indicated that minute amounts of misfolded SOD1 enriched in the motor areas might exert the ALS-causing cytotoxicity. A hydrophobic interaction chromatography (HIC) protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
156
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(173 citation statements)
references
References 32 publications
(52 reference statements)
14
156
2
Order By: Relevance
“…Here we identified misfolded mutant SOD1 as a diseaseassociated endogenous danger signal that is sensed by microglia and initiates inflammation through caspase-1-dependent IL-1β maturation. Mutant SOD1 has been described to form amyloidlike oligomers and aggregates in vitro and in vivo (3,(19)(20)(21). We demonstrate that the degree of amyloid-like misfolding of mutant SOD1 correlated with IL-1β maturation, supporting the recent finding that SOD1 aggregate formation is linked to accelerated disease progression in ALS patients (22).…”
Section: Discussionsupporting
confidence: 74%
“…Here we identified misfolded mutant SOD1 as a diseaseassociated endogenous danger signal that is sensed by microglia and initiates inflammation through caspase-1-dependent IL-1β maturation. Mutant SOD1 has been described to form amyloidlike oligomers and aggregates in vitro and in vivo (3,(19)(20)(21). We demonstrate that the degree of amyloid-like misfolding of mutant SOD1 correlated with IL-1β maturation, supporting the recent finding that SOD1 aggregate formation is linked to accelerated disease progression in ALS patients (22).…”
Section: Discussionsupporting
confidence: 74%
“…However, in addition to the hypothesis that dimer destabilization causes aggregation, another hypothesis for aggregation is that newly translated fALS SOD1 causing variants never dimerize due to lack of intrasubunit disulfide formation, metal deficiency, etc., resulting in unstable monomers (58,59). Even if fALS variants never dimerize and exist as monomers in vivo (29)(30)(31), and thus C111 residues are rarely in close proximity to each other, our data with G85R suggest that this strategy may be an effective one.…”
Section: Discussionmentioning
confidence: 83%
“…A prevailing hypothesis for the mechanism of the toxicity of fALS-SOD1 variants involves dimer destabilization and dissociation into monomers, which then nucleate the formation of higher-order aggregates (13,(26)(27)(28). Indeed, variant proteins, such as the G85R SOD1 used in this study, are found as monomers in vivo (29)(30)(31). A number of modifications, including loss of Cu or Zn (32), cleavage of the native, intramolecular disulfide (33), oxidation (13,34), and fALS-associated mutation (35), predispose the SOD1 dimer to dissociate.…”
mentioning
confidence: 98%
“…We noted also that basal neutral α-glucosidase activity in WT mice is 1.7-and 4-fold greater in muscle and liver, respectively, vs. spinal cord. Both the basal-and disease-induced differences in neutral α-glucosidase activity within muscle and liver may explain in part why misfolded SOD1 protein was detected at significantly higher levels in CNS than in peripheral tissues in mouse ALS (43,44). Our point of emphasis is that this mouse ALS model displays significant glycogen increases in both CNS and peripheral tissues.…”
Section: Discussionmentioning
confidence: 98%